ANTIBIOGRAM PROFILE OF PATHOGENIC FUNGI ON SEIDENFIA RHEEDII LEAF EXTRACTS - T.FRANCIS XAVIER; S.R.SENTHIL KUMAR (International Journal of Pharma and Bio Sciences, 2013)
Antibiogram profile of various pathogenic fungi on different solvent extracts of Seidenfia rheedii leaf were evaluated using the paper disc agar diffusion method by measuring the diameter of the growth inhibition zones. Among various solvent extracts tested, ethanol leaf extracts exhibited greater inhibition followed by ethyl acetate and chloroform solvent extracts. The petroleum ether, ethanol (1: 1) showed a low degree of inhibition on test fungi whereas no activity was associated with aqueous extract of Seidenfia rheedii. The zones of inhibition for each extract was compared with standard antibiotics. The inhibition zones of each solvent extracts found to be either less than or nearly equal to the inhibition zones of standard antibiotics. The leaf extracts showed greater inhibition than the other parts used<s>)</s>.From the results achieved there appears to be a rationale for the use of this plant to combat infectious diseases, Seidenfia rheedii had an inhibitory effect on the pathogenic fungi causing infections in human beings. Hence, Seidenfia rheedii would be the effective plant as it demonstrated good activity against fungi. This would add merit to its traditional use in the treatment of infectious diseases.